Enhancing Impulse Buying in the Retail Industry: The Mediating Role of Positive Emotions - Rahmania, Lorianur; Novita Sari, Puspa (Journal of Accounting and Finance Management, 2025)
Unplanned purchases make retail growth experience rapid growth. With positive emotions acting as an intervening variable, the aim of this study is to examine how visual merchandising and store atmosphere affect impulsive buying. In this study, the data analysis technique used is quantitative path analysis with questionnaires distributed to 175 respondents with certain criteria, using purposive sampling. This research indicates that Visual Merchandising and Store Atmosphere both positively contribute to Positive Emotions. While Positive Emotions directly enhance Impulse Buying, neither Visual Merchandising nor Store Atmosphere have a direct impact on it. Instead, they influence Impulse Buying indirectly through Positive Emotions.